Implementation of a Health Accessible to the Deaf: Training of Health Professionals in Brazilian Sign Language (LSB) (Research, Society and Development, 2022)
The right to deaf health quality and information in Brazil, have been given great prominence from the recognition of Law nº 10.436 of 2002 and Decree nº 5.622 of 2015 that support the deaf communities in the country the right to use the Brazilian Sign Language Signs - LSB. However, the integration of the deaf is still hampered not only by historical prejudice established over the centuries of segregation, as well as the lack of qualified health professionals to meet the public. The aim of this study is to emphasize through surveys of the data indicated the actual demonstration of the need for training of health professionals in Brazilian Sign Language (LSB) to effect quality with a health service to a deaf patient. Applied a questionnaire with 10 questions were interviewed 50 health professionals (listeners) aiming to clarify the issues that interfere with driving a good of care in the health units. The results of the questionnaire showed there is a lack of preparation of professionals to deal with deaf patients users of LBS, accentuating the difficulties faced by deaf individuals, who do not get a quality service. The data were used to propose the LSB course for distance health professionals, which will be available as an extension of the course, which will be available on the site of Telessaúde UERJ, contributing to improve the knowledge of the deaf and LSB by the health professional and assisting in the provision of quality and integration for deaf patients, strengthening the LIBRAS legislation.